Experimental and analytical investigations on seismic behavior of corroded reinforced concrete members - Vu Ngoc Son (2018)
Corrosion of reinforcement is recognized as one of the major deterioration problems for the reinforced concrete (RC) structures which seriously affects their serviceability and durability. Reinforcement corrosion happens in RC structures due to the carbonation of concrete or diffusion of chloride. A large number of RC building and bridge structures in the coastal areas are under serious chloride attack, and even more so the humid and sultry environment in these regions could further speed up the corrosion process of reinforcement. Therefore, there has been rising concern to assess the durability and safety of these existing corroded structures, especially when they are subjected to seismic loading. The aim of this study is to investigate the seismic behavior of reinforced concrete members in corrosive environments, including the stress-strain relations of confined concrete with corroded transverse reinforcement and the seismic performance of RC slender and short columns with corroded reinforcement.